2018
DOI: 10.1080/17518253.2018.1445301
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles by seed of Phoenix sylvestris L. and their role in the management of cosmetics embarrassment

Abstract: Recently, green synthesis of silver nanoparticles has attracted much curiosity in the field of life science research. In the present study, we have reported a green method for synthesis of silver nanoparticles (AgNPs) using aqueous seed extract of Phoenix sylvestris L. The green synthesized nanoparticles were characterized by aids of dynamic light scattering, scanning electron microscopy, transmission electron microscopy, X-ray diffraction, and Fourier transform-infrared.Further, the study demonstrate the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Notably, the CB seed AgNPs exhibited better reducing power than the standard Ascorbic acid as the extract was enriched with phytoconstituents. Still, the phytoconstituents like phenols also possess electron-donating antioxidant capacity (Qidwai et al, 2018). This result is in agreement with the attempt of (Dipankar et al, 2012), who reported similarly in Caesalpinia bonducella leaves AgNPs.…”
Section: Ferric (Fe 3+ ) Reducing Power Assaysupporting
confidence: 90%
“…Notably, the CB seed AgNPs exhibited better reducing power than the standard Ascorbic acid as the extract was enriched with phytoconstituents. Still, the phytoconstituents like phenols also possess electron-donating antioxidant capacity (Qidwai et al, 2018). This result is in agreement with the attempt of (Dipankar et al, 2012), who reported similarly in Caesalpinia bonducella leaves AgNPs.…”
Section: Ferric (Fe 3+ ) Reducing Power Assaysupporting
confidence: 90%
“…The DPPH free radical scavenging activity of SeNPs was determined using the method described here ( Qidwai et al, 2018 ) Typically, different concentration (10–50 μg/ml) of nanoparticles was mixed with 1 ml of 0.1 mM DPPH in methanol solution and 450 µl of 50 mM Tris-HCl buffer(pH 7.4), and incubated for 30 min. After incubation, the reduction in the number of DPPH free radicals was measured based on the absorbance at 517 nm.…”
Section: Methodsmentioning
confidence: 99%
“…As the size of the particles was found to be function of the concentration of DSE, hence the DSE appeared to play a key role in controlling the size of particles 46,47 . These results were found to be in line with the previous literature indicating the role of DSE as size and shape modifying agent 35 .…”
Section: Transmission Electron Microscope (Tem) and Contact Angle Measurementsmentioning
confidence: 95%